An all-deoxyribonucleic acid circuit for detection of human telomerase activity in solution and on paper - Zhou, Zhixue; Gu, Jimmy; Brennan, John D.; Li, Yingfu (Frontiers in Analytical Science, 2022)
We report on the design of a simple all-DNA circuit with dual functions of signal amplification and signal reporting and its use for detection of human telomerase activity from cancer cells. The system utilizes a catalytic hairpin assembly (CHA) reaction for amplification, which produces split G-quadruplex outputs that assemble to form complete guanine quadruplex (Gq) structures as reporting modules. As designed, a linear DNA sequence (the target) functions as a catalyst to drive cyclic programmed assembly of two hairpins, producing a DNA duplex with two guanine-rich sequences that assemble to form a complete Gq structure. The formation of the Gq element allows either fluorescence or colorimetric detection of the target. Examples are provided to demonstrate fluorescence detection of cancer cells’ telomerase activities in solution and the first example of a CHA-modulated colorimetric assay for detecting telomerase activities of cancer cells using a simple paper device.